Mecanismos neuroendócrinos envolvidos no controle da secreção de prolactina e em sua ação ansiolítica - Patricia Costa Henriques (2021)
Prolactin (PRL) is a pituitary hormone that exerts many functions besides its essential role in lactation, such as the modulation of the hypothalamus-pituitary-gonadal (HPG) axis and anxious behavior. In the present work, we investigated the neuroendocrine mechanisms related to these two functions of PRL. In the first study, we evaluated the mechanism involved in estradiol (E2)-induced PRL surge. Ovariectomized (OV) rats were treated with oil or two doses of E2, which resulted in low (OVE-4) and high (OVE-80) physiological levels of this hormone. Both E2 doses promoted surges in PRL secretion similarly to proestrus (PRO), which did not occur in OV or diestrus (DI) rats. The enzymatic activity of dopaminergic neurons, measured by phosphorylated tyrosine hydroxylase (TH) labeling, was reduced only in OVE-80 rats, but did not differ between DI of PRO, which indicated that change in this activity is not determinant for the PRL surge genesis. Analysis of c-Fos expression in the preoptic area, periventricular nucleus and paraventricular nucleus (PVN) of the hypothalamus also did not demonstrate neuronal activation related to increased PRL secretion. However, neurochemical analysis of dopamine (DA) and 3,4-dihydroxyphenylacetic acid (DOPAC) concentrations revealed a pattern of daily reduction in the activity of neuroendocrine dopaminergic terminals regardless of E2 levels. On the other hand, both E2 doses were able to alter the expression of key genes for the control of PRL in the pituitary, including reduction of D2 receptor and increase of oxytocin (OT) receptor. Thus, these data suggest that the E2-induced PRL surge in female rats depends essentially on the daily reduction in dopaminergic inhibitory tone associated with E2 effect of altering lactotrophs responsiveness to hypothalamic inhibitory and stimulatory inputs. The second study of our work aimed to evaluate the effect of PRL on anxiety, and the possible central mechanisms involved in this action. Intracerebroventricular trarment of rats with PRL confirmed its anxiolytic effect, which we observed to have dose-response in inverted U profile, and does not depend on the presence of sex steroids. Imunohistochemical analysis of phosphorylated transducer and activator of transcription proteins 5 (STAT5) revealed that, among the brain areas responsive to PRL, PVN neurons were the ones that presented the same dose-dependent profile of its anxiolytic effect. Administration of antagonists for PRL and OT receptors blocked PRL anxiolytic effect, showing that the activation of them both is essential in mediating this effect. Finally, the evaluation of Fos immunoreactivity in rats subjected to restraint stress demonstrated that, in fact, PVN activation in respose to stress is blocked by PRL. Thus, our study demonstrates that PRL anxiolytic action is mediated by the inhibition of PVN activity and that OT neurons play an essential role in this mechanism.